Centralized COVID-19 Contact Tracing in a Home-Rule State. (November 2022) - Macomber, Kathryn; Hill, Ashley; Coyle, Joseph; Davidson, Peter; Kuo, Jeremy; Lyon-Callo, Sarah
Contact tracing is an evidence-based intervention to control many communicable diseases, including COVID-19. Before the COVID-19 pandemic, contact tracing in Michigan focused on HIV, sexually transmitted infections, and tuberculosis, and it was conducted by state and local health department staff. Within 2 weeks of the first reported COVID-19 cases in Michigan in March 2020, the existing public health workforce was overwhelmed by the need for contact tracing and daily symptom monitoring. This case study narrates the development of a staffing plan that included volunteers and contractual staff to conduct centralized contact tracing in a home-rule state (ie, a state in which local health departments have full authority and autonomy under public health code to conduct the functions necessary to prevent disease, including contact tracing). This case study details various training, workforce management, and technology tools that were used. During the study period (May 2020–June 2021), contact tracers called 432 218 contacts and 269 439 were successfully reached, 48 134 of whom reported developing symptoms. The most important lesson learned was the need for more automated processes to improve efficiency in processing volunteer applicants, training, and scheduling. Nonetheless, the centralized workforce was successful, was flexible, and met the changing demands in Michigan.